AUDIT OF REQUESTS AND USAGE OF FRESH FROZEN PLASMA IN A TERTIARY CARE HOSPITAL - Dr. Rohini Prabhakarrao Shewale; Dr. Pranita Bhikulal Sontakke; Dr. Meera Mahajan; Dr. Chandrashekhar Prabhakar Bhale (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Fresh Frozen Plasma (FFP) is a vital blood component used for hemostasis in cases of clotting factor deficiencies, coagulopathy, or ongoing bleeding. Even with stringent guidelines, its usage is often inappropriate, leading to increased costs and risks. This study audits FFP utilization in a tertiary care hospital to assess adherence to established guidelines and identify areas for improvement. Method: A retrospective study was conducted over one year at a tertiary care hospital in Maharashtra. Data was collected for patients for whom FFP units were requested and transfused. Records reviewed included patient demographics, indications for FFP use, coagulation profiles, and departmental requests. Compliance with College of American Pathologists (CAP) guidelines was evaluated, and statistical analyses were performed. Results: In this study a total of 381 patients were studied. The majority of FFP use was for surgical procedures (51.97%) and bleeding (23.88%) patients. The Cardiothoracic& Vascular Surgery department received maximum FFP units (35.43%). PT results were available for 60% of cases, with 25% showing deranged PT, indicating potential overuse in cases with normal PT values. Conclusion: The audit reveals a significant discrepancy between FFP requests and issuance, highlighting potential over-requesting and stringent issuance criteria. Most FFP were used appropriately for surgery and bleeding, though there were instances of its use without clear indications. Regular audits and adherence to guidelines are crucial for optimizing FFP use and improving transfusion practices.